HSBC in East Asia (before the 2008 credit crunch) - Rowley, Chris, 1959-; Poon, Irene H.; Zhu, Ying, 1961-; Warner, Malcolm ([London] : SAGE, 2016)
We are given an example of how human resources management (HRM) is practiced within the increasingly important East Asian financial markets. We look at HSBC bank's training and developing programmes, as well as the company's recruitment practices within the cultural challenges of a globalized economy.
Originally Published in: Harzing, A. W., & Pinnington, A. (2011). HSBC in East Asia (Before the 2008 Credit Crunch). In International human resource management (3rd ed., pp. 174-182). London: SAGE Publications Ltd. Print. ISBN: 9781847872937.
Description based on online resource; title from home page (viewed on April 21, 2016).
Keywords: elektronické knihy; electronic books; Hongkong and Shanghai Banking Corporation; Personnel management -- Asia, East -- Case studies; Banks and banking -- Personnel management -- Case studies